A new species of Sisyrinchium (Iridaceae) from the state of Guanajuato, Mexico - Ceja-Romero, Jacqueline; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2009)
Sisyrinchium guanajuatense is described and illustrated. The new species is known only from the state of Guanajuato, Mexico. It belongs to the subgenus Echthronema and is compared with some species of the S. schaffneri complex to which it relates. An identification key for all these taxa is included.